Leasing from the perspective of environmental management and its influence on business performance - Bocok, Vojtech; Hinke, Jana; Abrham, Josef (Frontiers in Environmental Science, 2023)
Goals: The paper aims to analyze the current development in the field of circular economy relating to the use of lease financing as possible environemental management’s tool. Methods: The paper contains own research conducted on companies trading on the Prague Stock Exchange from 1993 to 2019, in which the influence of lease financing on market values of companies representing investor confidence and profitability ratios are examined. The research uses a regression model of panel data. Results: The research confirms the fact that companies using leases are able to maintain investor confidence better. There has been an increase in their market value. It has been proved that lease financing does not harm the economic performance of companies and that, on the contrary, it is a possible way of financing companies, which would be more in line with sustainable development. Conclusion: The presented article extended further quantitative research in the field of sustainability, circular economy, environmental management and the position of leasing as one of the possible instruments of these policies. It has been confirmed that the use of leases increases the value of Tobin’s Q. However, there has been a decrease in investor confidence expressed by the negative correlation of Tobin’s Q when comparing with the situation where the company invests in increasing its tangible assets in the standard way.